What can be observed in intervertebral cartilage endplate with aging? An animal model study of excessive axial mechanical loading - Hu, Zhouyang; He, Fan; Li, Xinhua; Jiang, Bei; Yan, Shuaifeng; Tan, Jun; Li, Lijun (Frontiers in Medicine, 2024)
Introduction The cartilage endplate (CEP) plays a crucial role as both a mechanical barrier and nutrient channel for the intervertebral disc, but it is vulnerable to excessive axial loading. We modified the Ilizarov external fixator and applied it to the CEP of the rat tail to impose diurnal, controllable excess axial loading. The objective was to measure morphological changes in the CEP when subjected to loading during the aging process. Methods Two Kirschner wires were, respectively, inserted into the center of the eighth and ninth coccygeal vertebrae (Co8/9) of rat (n = 54) to apply axial loading to the CEP. A remote control device was used to establish the diurnal loading schedule. At the end of 4, 8, and 12-week periods, the Co8/9 CEPs in each group were analyzed using MRI, histological staining, and immunohistochemical staining techniques. Results The novel Ilizarov model that we modified successfully induced degeneration of the rat coccygeal CEP. MRI analysis revealed significant degenerative changes in the loaded Co8/9 CEP, including decreased signal intensity and the formation of Schmorl’s nodes at 8 and 12 weeks. Histological examination showed progressive CEP degeneration (CEPD), characterized by decreased microporosity, thinning, and structural irregularities. Immunohistochemical analysis demonstrated a significant reduction in Aggrecan and Collagen II expression in the CEP and nucleus pulposus over time. Control and sham groups maintained normal CEP structure and composition throughout the study period. Conclusion Excessive axial loading induced CEPD in the rat tail, primarily characterized by the formation of Schmorl’s nodes and a reduction in CEP microporosity in this study. Our modified Ilizarov rat tail compression model, featuring stable and controllable axial loading capabilities, provided an alternative experimental paradigm for further investigation into CEPD.